ANALISIS KANDUNGAN GIZI SINOLE TERI YANG DI TAMBAHKAN DENGAN IKAN TERI NASI DAN DAYA TERIMANYA - Rince wenda; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Sago is one of the potential traditional sources that can be developed in food diversification supporting local and national food security. Anchovy is one of the marine living resources available in almost all Indonesian waters and is one of the leading export commodities from the fishery sub-sector. Sinole is a staple food in the likes of children and even adults, especially in eastern Indonesia And is one of the most popular and trendy cakes in Maluku and Papua. Sinole is generally made with additives such as sugar, coconut, and raw sago that can give a distinctive taste of sago itself. The purpose of this study was to determine the differences in acceptability and nutritional value including calcium, phosphorus and carbohydrate from the mixture of sago and anchovy with a ratio of 60%: 40% and 70%: 30% with one type of white sago. This research is an experimental research with randomized block design which is divided into two treatments: 60%: 40% and 70%; 30%. test and acceptance is done to 30 student papua who study at University of North Sumatra field and nutritional analysis done in laboratory of research city and standardization of field industry. The result of this research shows that the test of receipt of anchovy that has the best receptivity is sinole teri which is made from the mixture of sago and anchovy with ratio of 70% raw sago and 30% of the anchovy. Nutritional value per 100 grams of carbohydrates (26.6 grams), phosphorus (29.06 mg) and Calcium 20.25 mg). Suggest to consumers to make sinole anchovy sago and anchovy to increase the varieties of the existing teri cinnamon as well as one of the alternative processed foods with more nutritional value. Keywords: sago,anchovy,sinole teri,receiving power,nutritional value.